2022
DOI: 10.3389/fmicb.2022.1045206
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Acinetobacter baumannii: A challenge in the intensive care unit

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) has become one of the leading causes of healthcare-associated infections globally, particularly in intensive care units (ICUs). Cross-transmission of microorganisms between patients and the hospital environment may play a crucial role in ICU-acquired CRAB colonization and infection. The control and treatment of CRAB infection in ICUs have been recognized as a global challenge because of its multiple-drug resistance. The main concern is that CRAB infections ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 132 publications
(156 reference statements)
1
16
0
Order By: Relevance
“…22 Patients in the ICU were at risk for infection due to delayed immune responses, reduced host defense systems, and the use of invasive devices such as central venous catheterization, mechanical ventilation, and urinary tract catheterization. 21 It is consistent with this study which found that the use of invasive medical devices was most common in patients treated in the ICU, namely peripheral venous catheters (52.3%), mechanical ventilation (50.7%), and nasogastric tubes/orogastric tubes (54.7%). These percentages were higher than those in other wards.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…22 Patients in the ICU were at risk for infection due to delayed immune responses, reduced host defense systems, and the use of invasive devices such as central venous catheterization, mechanical ventilation, and urinary tract catheterization. 21 It is consistent with this study which found that the use of invasive medical devices was most common in patients treated in the ICU, namely peripheral venous catheters (52.3%), mechanical ventilation (50.7%), and nasogastric tubes/orogastric tubes (54.7%). These percentages were higher than those in other wards.…”
Section: Discussionsupporting
confidence: 90%
“…A high Pitt Bacteremia score, the ICU, and a high Charlson comorbidity index have been associated with a high mortality rate. 2,21,26 This study suggests that giving appropriate empiric therapy does not influence the mortality rate because early mortality (0-5 days after blood sampling of patients with CRAB) were excluded from this study because there was no definitive antibiotic considering this study analyzed patients who received empirical and definitive antibiotics. A study conducted on patients treated in the ICU of a hospital in Turkey revealed that the late administration of adequate empiric therapy increased the mortality rate (> 3 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism of action can reduce the release of lipopolysaccharide during bacteriolysis, providing good biological safety ( Rodloff et al, 2006 ; Zhanel et al, 2007 ; Nowak and Paluchowska, 2016 ). However, with the wide application of carbapenem antibiotics in recent years, the drug resistance rate of A. baumannii to carbapenems has increased year by year ( Jiang et al, 2022 ). Polymyxins are effective for treating A. baumannii infection, with low rates of resistance, but are associated with a higher risk of nephrotoxicity ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that once Acinetobacter exhibits resistance to carbapenems, it usually has acquired several other antibiotic resistances, often including sulbactam [ 13 ]. To date, the resistance to sulbactam requires the addition of a second agent with a consequent potential increase of toxicity (e.g., nephrotoxicity with polymyxins) with no robust benefit on outcomes.…”
Section: Introductionmentioning
confidence: 99%